Physical, mechanical and thermal behavior of concrete block stabilized with glass fiber reinforced polymer waste (Research, Society and Development, 2020)
The Glass Fiber Reinforced Polymer (GFRP) waste despite having excellent physical and mechanical properties is still largely unexplored besides presenting large volume of waste with very low degradability. The use of concrete block presents high resistance to compression, low price high masonry coating ratio by material weight, however high thermal conductivity. Therefore, the study aimed to produce and investigate the effect of adding GRFP residues to concrete blocks due to physical, mechanical and thermal properties. The compositions were made by replacing the fine gravel between 0 to 10% in mass by the GFRP residue. They were evaluated from physical, mechanical and thermal tests. The results showed that the use of GFRP residue did not interfere in water absorption and compressive strength, despite the significant increase in mechanical energy absorption of the material. Thermal conductivity reduced by 46% and the concrete blocks were 7% lighter. In addition to providing a destination for a considerable quantity of the waste, the commercial value of the final product is higher due to using a residue with low degradability and high energy power due to burning during recycling.